Electrochemical Dehydrogenative Cross‐Coupling of Quinoxalin‐2(1H)‐ones with Amines for the Synthesis of 3‐Aminoquinoxalinones - Li, Ke‐Jing; Xu, Kun; Liu, Yong‐Guo; Zeng, Cheng‐Chu; Sun, Bao‐Guo (Advanced synthesis & catalysis, 2019)
An efficient protocol for the synthesis of 3‐aminoquinoxalinones via the electrochemical dehydrogenative C‐3 amination of quinoxalin‐2(1H)‐ones was developed. With aliphatic amines and azoles as the nitrogen sources, a series of 3‐aminoquinoxalinones was obtained in up to 99% yield. This direct electrolytic method avoids the use of transition metals and external oxidants, and represents an appealing alternative for the synthesis of 3‐aminoquinoxalinones.